Analisis Pengadaan Logistik Farmasi dengan Metode Konsumsi di Rumah Sakit PKU Muhammadiyah Gamping - Tri Wahyuni; Rochana Ruliyandari (International Journal of Healthcare Research, 2020)
The consumption method is a method carried out by evaluating the use of past drugs as a basis for determining the estimated needs, then adjusted to the strategic plan of the hospital and hospital pharmacy, so that the final result is a list of drug needs. This study aims to analyze the pharmmaceutical logistics needs of consumption methods at PKU Muhammadiyah Gamping Hospital. The type of research used in this research is qualitative research with phenomenology approach and the subject of research are 3 people. Data collection uses indepth interviews and observation. Test the validity and credibility of data in this study using triangulation sources and techniques. Based on the results of this study indicate 1) The largest average use was Candesartan 16 mg of 48,398 tablets, 3) Lead time was adjusted for PBF and assessed by score. 4) The amount of safety stock is proportional to the average number of uses per month. 5) The results of the calculation of the total amount of drug needs for the 2020 period with the method of consuming the five types of drugs have more drug needs than the stock in storage so it needs to be added to meet the needs. The results of the calculation of the total amount of drug needs in 2020 with consumption methods that need to be provided for Candesartan 16 mg are 731,078 tablets, Metformin 500 mg are 713.444 tablets, Candesartan 8 mg are 348.804 tablets, Thrihexyphenidyl are 285.138 and Clopidogrel 75 mg are 313.548 tablets.